The Relationship Between Physical Activity and Fruit and Vegetable Consumption with the Risk of Type 2 Diabetes Mellitus in Adults Aged 30–60 Years - Asih Fatriansari; Indria Pijaryani; Maxianus K. Raya (CV. Get Press Indonesia, 2025)
This study aimed to analyse the relationship between physical activity and fruit and vegetable consumption with the risk of Type 2 Diabetes Mellitus (T2DM) among adults aged 30–60 years in Temanggung Regency, Indonesia. A cross-sectional design was employed using primary data collected through a structured questionnaire covering physical activity, fruit and vegetable intake, and diabetes risk assessment. Bivariate and multivariate analyses were applied to determine the strength and direction of associations. The findings indicated a significant relationship between physical activity and T2DM risk (p = 0.015), as well as between fruit and vegetable consumption and T2DM risk (p = 0.010). Adults with low physical activity and those consuming fewer than five servings of fruits and vegetables per day were more likely to develop T2DM than those meeting the recommended levels. These results highlight that adequate physical activity and sufficient fruit and vegetable intake are crucial in preventing non-communicable diseases, particularly type 2 diabetes. Such behaviours contribute to improved insulin sensitivity, glucose metabolism, and reduced insulin resistance—key mechanisms in diabetes development. The findings are expected to inform the design of more effective, sustainable, and contextually relevant diabetes prevention programmes in Indonesia.